PENERAPAN REGRESI LOGISTIK BINER UNTUK MENGUKUR RESIKO ANEMIA DENGAN STATUS GIZI IBU HAMIL - Suhardi, Deddy A; Fadila, Ila (Jurnal Matematika Sains dan Teknologi, 2016)
The prevalence of anaemia is an important health indicator for pregnant women. This paper demonstrates the use of logistic regression modelling techniques for an ordinal binary in terms of both response and predictor variables. By using 120 cross-sectional data to measure the attitude of pregnant women observed at three Community Healthcare Center (CHC) in the Serang District - Banten Province on September 2012, we investigated a factor predicting anaemia and tested whether changes in nutritional status were associated with changes in anaemia status. The anaemia status threshold using haemoglobin concentration (g/dl) was measured by the Cyanmethemoglobin method, and the nutritional status was categorized by measuring Upper Arm Circumference (cm). This paper discusses the roles of nutritional status determining the risks of anaemia and compares the results obtained using the contingency analytical methods. The paper also demonstrates how the logistic regression modelling approach dealing with the odds ratio statistic can better explain the risks of anaemia determined by nutritional status found in the CHC studied. We found that anaemia status is affected by nutritional status (coef. 1,07; p. 0,066), and the results of contingency analysis reveals that anaemia satus is associated with nutritional status (chi-sq. 3,60; p. 0,058). According to odds ratio statistic of the logistic regression (OR 2,92), the risks of anaemia on pregnant women with cronic energy deficiency would be 2,92times higher than they are on normal nutritions.   Prevalensi anemia pada kehamilan merupakan salah satu indikator penting kesehatan ibu hamil. Paper ini membahas teknik regresi logistik untuk mengukur resiko anemia ibu hamil berdasarkan status gizinya. Rancangan model hanya terdiri dari satu variabel respon dan satu prediktor skala biner. Hasil analisis regresi logistik dibandingkan dengan analisis chi-kuadrat tabel kontingensi. Estimasi parameter regresi menggunakan data cross-sectional 120 ibu hamil yang diamati langsung dari tiga Puskesmas di Kabupaten Serang, Banten, pada September 2012. Status anemia dikategorikan dari pengukuran kadar hemoglobin (g/dl) menggunakan metode cyanmethemoglobin, sedangkan status gizi dari pengukuran pita lingkar lengan atas (cm). Analisis regresi logistik menunjukkan satus anemia dipengaruhi status gizi (koefisien regresi status gizi 1,07; odds ratio 2,92; p. 0,066). Analisis chi-kuadrat menunjukkan status anemia berhubungan dengan status gizi (chi-kuadrat 3,60; p. 0,058). Statistik odds ratiopada kasus ini mendeskripsikan sejauh mana peran status gizi menentukan resiko anemia ibu hamil. Resiko anemia 2,92 kali lebih tinggi bagi ibu hamil dengan kondisi gizi kurang energi kronik daripada ibu hamil dengan gizi baik.